Case report: Rudimentary uterine horn with ovarian endometriosis manifested as pelvic ectopic kidney - Yin, Si-fan; Chai, Jia-gui; Feng, Run-lin; Yin, Zhi-yuan; Zhao, Shen-zhao; Zhang, Tao; Ke, Chang-xing (Frontiers in Medicine, 2023)
Background: The unicornuate uterus is a rare congenital uterine malformation. Unicornuate uterus with rudimentary horn, ovarian endometriosis, and congenital renal agenesis are unusual combinations that are easily misdiagnosed due to the lack of typical clinical manifestations. Case summary: This patient was a 19-year-old female. She was admitted to the hospital after one month for pelvic pain. Physical examination was unremarkable. B-ultrasound and CT scan both indicated pelvic ectopic kidney. In addition, renal scintigraphy revealed normal perfusion and function of the right kidney, but the perfusion and function of the left kidney were not visible. We combined with preoperative images and diagnosed a left pelvic ectopic kidney. A laparoscopic left pelvic ectopic nephrectomy was performed after adequate surgical preparation. However, the postoperative pathological diagnosis was a rudimentary uterine horn with endometriosis and congenital renal agenesis. Fortunately, she recovered and was discharged from the hospital five days after surgery. Moreover, she received regular follow-ups at the gynecology clinic, and the gynecologist added leuprolide acetate to prevent the recurrence of endometriosis. To date, no right adnexal or uterine abnormalities were detected on ultrasound at the follow-up visit. Conclusion: Rudimentary uterine horn with endometriosis and congenital renal agenesis are rare and easily misdiagnosed due to the lack of typical clinical manifestations. A gynecological examination is recommended for patients who may have this disease.